Copts in context : negotiating identity, tradition, and modernity - Doorn-Harder, Pieternella van, 1956- (Columbia, South Carolina : University of South Carolina Press, 2017)
A comprehensive examination of this deeply traditional Christian religion as it confronts modernity.
Identity in Transition -- Challenges of the Diaspora -- Tradition.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on September 29, 2017).
Added to collection customer.56279.3
Keywords: Coptic Church; Coptic Church; Copts; RELIGION -- Christianity -- Orthodox; HISTORY -- Middle East -- Egypt; Copts; Electronic books